(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Grouped Rural Primary School (CRA) it requires practices and dynamics different to urban schools. That’s why we assume different work methods. We will develop a videogame that reinforces learning and developing of intellectual capacities in an autonomous way, where each pupil/user will choose and build their own knowledge path.